Images of Virtue: Reading, Reformation and the Visualization of Culture in Rousseau’s La Nouvelle Héloïse - Landauer, Michelle (Romanticism on the Net, 2007)
AbstractThis essay explores the visualization of culture in the late eighteenth and early nineteenth centuries by examining the spectacle surrounding the death of a beautiful woman in sentimental texts. Focusing on Rousseau’s Julie, ouLa Nouvelle Héloïse, I argue that this novel highlights the relationship between interpretation and identity formation by outlining a style of reading that concentrates on the visual aspects of interpretation. Central to my study is the idea that Rousseau considered the imagination as the primary medium through which interpretation occurred. This is an unstable medium in that the passions were believed to influence the imagination and limit one’s ability to read properly. Rousseau thus sought to repress passion and contain the imagination through an image presented in the form of a spectacle – the image of the feminine ideal. This image, stabilized in death, needed to be internalized in the reader’s heart and mind. Readers would then interpret bodies/texts/objects – and their own identity – through an imagination that is controlled by this enduring symbol, allowing them to have access to “truth,” and to regain a sense of unity and happiness that is often lost in modern society.